2018
DOI: 10.1590/1678-4162-9412
|View full text |Cite
|
Sign up to set email alerts
|

Coinfecções por Leishmania infantum, Neospora caninum e Toxoplasma gondii em cães necropsiados da região central do Rio Grande do Sul, Brasil

Abstract: RESUMO O objetivo do presente trabalho foi determinar a presença de anticorpos para Leishmania infantum, Neospora caninum e Toxoplasma gondii, por meio da reação de imunofluorescência indireta (RIFI), em cães (n=78) provenientes da região central do Rio Grande do Sul, necropsiados no Hospital Veterinário da Universidade Federal de Santa Maria (UFSM), bem como avaliar os dados epidemiológicos, sazonais e anátomo-histopatológicos. Do total de animais avaliados, 67,9% (53/78) apresentaram soropositividade para ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…It has now been established that the consumption of commercial food by dogs has increased worldwide in recent years, which has contributed to a reduction in the transmission of some pathogens. Similarly, the frequency of infection by T. gondii (9.54%) was lower than previously reported in the same area (54.4%) 12 and in other studies conducted elsewhere 14 .…”
contrasting
confidence: 46%
“…It has now been established that the consumption of commercial food by dogs has increased worldwide in recent years, which has contributed to a reduction in the transmission of some pathogens. Similarly, the frequency of infection by T. gondii (9.54%) was lower than previously reported in the same area (54.4%) 12 and in other studies conducted elsewhere 14 .…”
contrasting
confidence: 46%
“…A high frequency of anti-T. gondii (62.9%) antibodies was also detected in dogs from a CanL-endemic area in the state of São Paulo, Brazil [33]. However, in studies conducted in areas not endemic for CanL in Brazil, the authors found frequencies of anti-Leishmania and anti-T. gondii antibodies of 11.6% in dogs from Londrina, state of Paraná [34], and of 10.2% in dogs from the central region of the state of Rio Grande do Sul [35]. These percentages are lower than those observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers used IFA and ELISA serological techniques to diagnose infection by T. gondii and E. canis, respectively, in 353 dogs from Bahia and found co-infection by these agents in 20.1% (71/353) of the evaluated animals. The relationship between co-infection by E. canis and T. gondii or N. caninum may be due to the opportunistic characteristics of the parasites (Ratzlaff et al, 2018).…”
Section: Molecular Diagnosis Of…mentioning
confidence: 99%
“…In these animals, the infection can http://dx.doi.org/10.1590/1678-4162-12907 Original Article -Veterinary Medicine either show no symptoms or have a major clinical presentation, particularly in immunocompromised individuals. The evaluation of the seroprevalence of this agent in canine species is of great importance because the diagnosis in these animals can reveal environmental and human contamination (Ratzlaff et al, 2018). In addition, dogs can act as definitive hosts of N. caninum which, in areas with cattle, can lead to severe economic losses because infection by this agent is mainly related to episodes of pregnancy loss in cows (Dubey et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation